High-efficiency inverted tandem polymer solar cells with step-Al-doped MoO3 interconnection layer - Liu, Jian; Shao, S.; Fang, G.; Wang, J.; Meng, B.; Xie, Z.; Wang, L. (Elsevier BV * North-Holland, 2014)
A highly transparent and physically robust step-Al-doped MoO3 layer was successfully utilized as the interconnection layer (ICL) to fabricate high-efficiency inverted tandem polymer solar cells (PSCs). The inverted tandem cell constructed by the same PCDTBT:PC70BM active layer showed a power conversion efficiency (PCE) of 6.88% with equivalent external quantum efficiency of nearly 80%, implying a high charge-collection efficiency in tandem structure. Incorporation of two sub-cells with complementary absorption spectra leads to further increase of PCE over 7.31%, which is the best results for tandem PSCs with PEDOT:PSS-free interconnection layer. © 2013 Elsevier B.V.